Fibrous Dysplasia Polyostotic: When Radiology Clarifies the Diagnosis - Ihssane Lahlou PhD; Sara Essetti PhD; Samia Obilat PhD; Fatima Chait PhD; Nourrelhouda Bahlouli PhD; Yousra Guelzim PhD; Siham El Haddad PhD; Nazik Allali PhD; Latifa Chat PhD (SAGE Publishing, 2024)
Fibrous dysplasia is a rare non-hereditary congenital condition characterized by 2 main forms: monostotic and polyostotic. Monostotic is the more common form, while polyostotic, often associated with a syndrome, is rarer. The case presented involves a 10-year-old patient who was diagnosed with polyostotic fibrous dysplasia accompanied by an endocrinopathy. This report explores the clinical and radiological aspects of this condition based on the patient's case.